(untitled) (Islamic Sciences Journal, 2025)
The research titled “Distribution of Duties in the Noble Prophetic Sunnah: An Analytical Study of the Hadith ‘Each of You Is a Shepherd, and Each of You Is Responsible for His Flock’” explores the prophetic tradition that emphasizes responsibility within society according to one’s position and capability. It highlights how tasks are distributed among individuals and discusses the great responsibility placed upon women regarding their husbands, children, and other obligations mentioned in the noble Hadith. The structure of the study consists of three sections: The first section presents preliminary definitions; the second section discusses the distribution of duties; and the third section provides an analytical study of the aforementioned Hadith. Finally, the research concludes with a summary of findings and a list of sources and references.